Development of a surgical competency assessment tool for sentinel lymph node dissection by minimally invasive surgery for endometrial cancer. Issue 5 (May 2021) - Moloney, Kristen; Janda, Monika; Frumovitz, Michael; Leitao, Mario; Abu‐Rustum, Nadeem R; Rossi, Emma; Nicklin, James L; Plante, Marie; Lecuru, Fabrice R; Buda, Alessandro; Mariani, Andrea; Leung, Yee; et al.
Abstract : Introduction : Sentinel lymph node dissection is widely used in the staging of endometrial cancer. Variation in surgical techniques potentially impacts diagnostic accuracy and oncologic outcomes, and poses barriers to the comparison of outcomes across institutions or clinical trial sites. Standardization of surgical technique and surgical quality assessment tools are critical to the conduct of clinical trials. By identifying mandatory and prohibited steps of sentinel lymph node (SLN) dissection in endometrial cancer, the purpose of this study was to develop and validate a competency assessment tool for use in surgical quality assurance. Methods : A Delphi methodology was applied, included 35 expert gynecological oncology surgeons from 16 countries. Interviews identified key steps and tasks which were rated mandatory, optional, or prohibited using questionnaires. Using the surgical steps for which consensus was achieved, a competency assessment tool was developed and subjected to assessments of validity and reliability. Results : Seventy percent consensus agreement standardized the specific mandatory, optional, and prohibited steps of SLN dissection for endometrial cancer and informed the development of a competency assessment tool. Consensus agreement identified 21 mandatory and three prohibited steps to complete a SLN dissection. The competency assessment tool was used to rate surgical quality in three preselected videos, demonstrating clear separation in the rating of the skill level displayed with mean skills summary scores differing significantly between the three videos (F score=89.4; P<0.001). Internal consistency of the items was high (Cronbach α=0.88). Conclusion : Specific mandatory and prohibited steps of SLN dissection in endometrial cancer have been identified and validated based on consensus among a large number of international experts. A competency assessment tool is now available and can be used for surgeon selection in clinical trials and for ongoing, prospective quality assurance in routine clinical care.